Efficacy and procedural efficiency of mechanical thrombectomy devices in posterior circulation stroke - Linlin Ma; Zhe Cheng; Gary B. Rajah; Gary B. Rajah; Ho Jun Yun; Xiaokun Geng; Xiaokun Geng; Xiaokun Geng; Yuchuan Ding (Frontiers in Neurology)
Background and purposePosterior circulation stroke patients have worse outcomes after mechanical thrombectomy (MT) and higher mortality than anterior circulation acute ischemic stroke (AIS) patients due to large vessel occlusions (LVOs). To determine the ideal recanalization device for posterior circulation LVO strokes, this study compared the operational parameters and prognosis among three commonly used thrombectomy devices.MethodsA total of 99 patients with posterior circulation AIS who underwent mechanical thrombectomy were enrolled. The patients were divided into three groups based on the different thrombectomy devices used during the procedure. Patient demographics, procedural metrics, functional outcomes, and symptomatic intracranial hemorrhage (sICH) were assessed. Any association between the devices and favorable clinical outcomes was assessed by logistic regression analysis.ResultsA total of 80 patients were analyzed. The Penumbra aspiration catheter revealed a significant advantage for the time of recanalization vs. the other devices (32 min vs. 44 and 41 min). No significant difference was observed in other procedural parameters or functional outcome. There was no significant difference in symptomatic cerebral hemorrhage (sICH), mortality, or functional independence after MT among the three groups. Diabetes mellitus, NIHSS score at admission, time from onset to recanalization, and occlusion site were associated with functional independence at 90 days, though the use of different recanalization devices did not make a significant difference.ConclusionAspiration achieved vessel recanalization faster than the retriever stent during mechanical thrombectomy in posterior circulation AIS. No clear improved functional outcome favored one device over another in this study. The key factors affecting functional outcomes in posterior circulation LVOs were the presence or absence of diabetes, baseline NIHSS, occlusion site of basilar artery, and TOR time.